Reliability-based safety evaluation of the BISTOON historic masonry arch bridge - Pouraminian, Majid; Pourbakhshian, Somayyeh; Noroozinejad Farsangi, Ehsan; Berenji, Sevil; Keyani Borujeni, Salman; Moosavi Asl, Mirhasan; Mohammad Hosseini, Mehdi (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This research examines the probabilistic safety assessment of the historic BISTOON arch bridge. Probabilistic analysis based on the Load-Resistance model was performed. The evaluation of implicit functions of load and resistance was performed by the finite element method, and the Monte-Carlo approach was used for experiment simulation. The sampling method used was Latin Hypercube.
Keywords: masonry bridge; arch bridge; probability of failure; sensitivity analysis; Monte Carlo simulation; epistemic uncertainty; most murowany; most łukowy; prawdopodobieństwo awarii; analiza wrażliwości; symulacja Monte Carlo